THE EFFECT OF FLEXIBLE WORK ARRANGEMENTS AND WORK-LIFE BALANCE ON INTENTION TO STAY: THE MEDIATING ROLE OF JOB SATISFACTION AND THE MODERATING ROLE OF PERCEIVED SUPERVISOR SUPPORT AMONG SALES EMPLOYEES OF AUTHORIZED CAR DEALERS IN MALANG CITY - Dewi Ayu Dyah Ningrum; Budi Eko Soetjipto; Wening Patmi Rahayu (RADJA PUBLIKA, 2026)
Sales employee retention constitutes a strategic concern in the automotive industry because sales work is characterized by demanding targets, commission-based earnings, intensive mobility, and relatively unpredictable working hours. This study examines the effects of flexible work arrangements and work-life balance on employees’ intention to stay, investigates the mediating role of job satisfaction, and assesses the moderating effect of perceived supervisor support. An explanatory quantitative approach with a survey design was employed. The population comprised 336 sales employees working for authorized car dealerships in Malang City. Using non-probability purposive sampling, 179 valid responses were obtained. Data were collected through a five-point Likert-scale questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling with SmartPLS 4.0. The results indicate that flexible work arrangements do not significantly affect job satisfaction, although they exert a positive effect on intention to stay. Work-life balance positively influences both job satisfaction and intention to stay, while job satisfaction significantly strengthens employees’ willingness to remain with their current organizations. The indirect-effect analysis reveals that job satisfaction does not mediate the relationship between flexible work arrangements and intention to stay. In contrast, it partially mediates the effect of work-life balance on intention to stay. The interaction tests further demonstrate that perceived supervisor support does not moderate the effects of flexible work arrangements, work-life balance, or job satisfaction on intention to stay. These findings suggest that work–life balance and job satisfaction constitute more substantial retention mechanisms, whereas flexible work arrangements primarily operate as instrumental job resources that facilitate the execution of sales responsibilities.